Hypoxic Induced Decrease in Oxygen Consumption in Cuttlefish (Sepia officinalis) Is Associated with Minor Increases in Mantle Octopine but No Changes in Markers of Protein Turnover - Capaz, Juan C.; Tunnah, Louise; MacCormack, Tyson J.; Lamarre, Simon G.; Sykes, Antonio V.; Driedzic, William R. (Frontiers in Physiology, 2017)
The common cuttlefish (Sepia officinalis), a dominant species in the north-east Atlantic ocean and Mediterranean Sea, is potentially subject to hypoxic conditions due to eutrophication of coastal waters and intensive aquaculture. Here we initiate studies on the biochemical response to an anticipated level of hypoxia. Cuttlefish challenged for one hour at an oxygen level of 50% dissolved oxygen saturation showed a decrease in oxygen consumption of 37% associated with an 85% increase in ventilation rate. Octopine levels were increased to a small but significant level in mantle, whereas there was no change in gill or heart. There were no changes in mantle free glucose or glycogen levels. Similarly, the hypoxic period did not result in changes in HSP70 or polyubiquinated protein levels in mantle, gill, or heart. As such, it appears that although there was a decrease in metabolic rate there was only a minor increase in anaerobic metabolism as evidenced by octopine accumulation and no biochemical changes that are hallmarks of alterations in protein trafficking. Experiments with isolated preparations of mantle, gill, and heart revealed that pharmacological inhibition of protein synthesis could decrease oxygen consumption by 32% to 42% or Na+/K+ ATPase activity by 24% to 54% dependent upon tissue type. We propose that the decrease in whole animal oxygen consumption was potentially the result of controlled decreases in the energy demanding processes of both protein synthesis and Na+/K+ ATPase activity.